Perancangan Sistem Informasi Pengumuman dan Broadcasting (NotifyCasting) - Muhammad Arqam; Syahputra, Muhammad Arqam; Hasbar, Fikri Anggara; Aslam, Dhiyaulhaq; Syukur, Pramudya Asoka (Journal of Security, Computer, Information, Embedded, Network, and Intelligence System, 2024)
Managing announcements and communication within a company often faces challenges in ensuring the effective and timely dissemination of information. This study aims to design and develop a web-based Announcement and Broadcasting Information System (NotifyCasting) to improve efficiency in information distribution within the company environment. The method used is the waterfall software development model, which includes the stages of requirement analysis, design, implementation, testing, and system maintenance. The results of the study show that the system successfully meets the functional and non-functional needs of the company by providing features such as real-time messaging and announcement delivery, audience filtering, and an accessible announcement archive. Testing with black box and white box methods indicates that the system functions according to the specified requirements, and the user interface is intuitive and easy to use. In conclusion, the NotifyCasting system can significantly enhance communication effectiveness within the company and can be adapted by other organizations for similar purposes.